Analysis Of Hadith On Hedonism With Zygmunt Bauman's Theory Of Liquid Society - Hadidsyah; M. Bik Muhtaruddin (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2025)
Hedonism, as a lifestyle oriented toward worldly pleasures, has become increasingly prevalent in modern society, including among Muslims. This way of life contradicts the Islamic principle of moderation, which emphasizes balance, self-control, and proportionality in fulfilling one’s needs. This study aims to reexamine the values of simplicity through a hadith-based analysis in response to the challenges of hedonism in contemporary society. The research employs a qualitative approach through a literature study, applying thematic hadith analysis (maudhu‘i) combined with concise takhrij to ensure the authenticity of the narrations. Hadiths concerning the prohibition of excessiveness and the encouragement of simple living are analyzed contextually using Zygmunt Bauman’s Liquid Society theory. The findings reveal that the Prophet’s teachings on simplicity emphasize the importance of controlling consumption, fostering social concern through sharing, and maintaining balance between material and spiritual needs. Meanwhile, Bauman’s concept of liquid modernity exposes how consumerist culture and rapid social changes have eroded the values of moderation. The contribution of this study lies in integrating Hadith analysis with Bauman’s theory, producing a contextual interpretation that is relevant for critiquing modern hedonism. The study concludes that the actualization of simplicity values in the hadith represents a strategic principle for building a more stable and civilized social order amid the dynamics of liquid modern society.